Chest compression duration influences outcome between integrated load‐distributing band and manual CPR during cardiac arrest. Issue 2 (27th August 2015) - Olsen, J.‐A.; Lerner, E. B.; Persse, D.; Sterz, F.; Lozano, M.; Brouwer, M. A.; Westfall, M.; van Grunsven, P. M.; Travis, D. T.; Herken, U. R.; Brunborg, C.; Wik, L.
Abstract : Background: The Circulation Improving Resuscitation Care (CIRC) Trial found equivalent survival in adult out‐of‐hospital cardiac arrest (OHCA) patients who received integrated load‐distributing band CPR (iA‐CPR) compared to manual CPR (M‐CPR). We hypothesized that as chest compression duration increased, iA‐CPR provided a survival benefit when compared to M‐CPR. Methods: A pre‐planned secondary analysis of OHCA of presumed cardiac etiology from the randomized CIRC trial. Chest compressions duration was defined as the total number of minutes spent on compressions during resuscitation and identified from transthoracic impedance and accelerometer data recorded by the EMS defibrillator. Logistic regression was used to model the interaction between treatment and duration of chest compressions and was covariate‐adjusted for trial site, patient age, witnessed arrest, and initial shockable rhythm. Primary outcome was survival to hospital discharge. Results: We enrolled 4231 subjects and of those, 2012 iA‐CPR and 2002 M‐CPR had complete outcome and duration of chest compressions data. While covariate‐adjusted odds ratio for survival to hospital discharge was 1.86 in favor of iA‐CPR (95% CI 1.16–3.0), there was an interaction between duration and study arm. When this was factored into the multivariate equation, the odds ratio for survival to hospital discharge showed a significant benefit for iA‐CPR vs. M‐CPR for chest compression duration greater than 16.5 min. Conclusion: After adjusting for compression duration and duration–treatment interaction, iA‐CPR showed a significant benefit for survival to hospital discharge vs. M‐CPR in patients with OHCA if chest compression duration was longer than 16.5 min.